Biogeochemical controls on ammonium accumulation in the surface layer of the TD: Southern Ocean - Smith, Shantelle (Department of Oceanography, 2023)
The production and assimilation of ammonium (NH₄⁺) are essential upper-ocean nitrogen (N) cycle pathways. However, in the Southern Ocean where the alternation between biological nitrate drawdown in summer and physical nitrate resupply in winter is central for setting atmospheric CO2, the active cycling of NH₄⁺ in the seasonally-varying mixed layer remains poorly understood. On a cruise from Cape Town (33.9°S) to the Marginal Ice Zone (MIZ; 61.4°S) in winter 2017, surface samples were collected and analysed for nutrient concentrations, planktonic community composition, size-fractionated rates of net primary production and N (as NH₄⁺, urea, and nitrate) uptake, and rates of NH₄⁺ oxidation. NH₄⁺ concentrations, measured every four hours, were five-fold higher than is typical for summer, and lower north than south of the Subantarctic Front (SAF; 0.01–0.26 µM versus 0.19–0.70 µM). Thus, showing that NH₄⁺ accumulates in the Southern Ocean's winter mixed layer, particularly in polar waters. NH₄⁺ uptake rates were highest near the Polar Front (PF; 12.9 ± 0.4 nM day-1 ) and in the Subantarctic Zone (10.0 ± 1.5 nM day-1), decreasing towards the MIZ (3.0 ± 0.8 nM day-1) despite the high ambient NH₄⁺ concentrations, likely due to the low temperatures and limited light. By contrast, rates of NH₄⁺ oxidation were higher south than north of the PF (16.0 ± 0.8 versus 11.1 ± 0.5 nM day-1), perhaps due to the lower light and higher iron concentrations characteristic of polar waters. Additional NH₄⁺ concentration measurements spanning the 2018/2019 annual cycle suggest that mixed-layer NH₄⁺ accumulation south of the SAF is due to sustained heterotrophic NH₄⁺ production in late summer through winter that outpaces NH₄⁺ removal by temperature-, light, and iron-limited microorganisms. The contribution by heterotrophic prokaryotes is supported by observations from winter 2017, where lower ratios of photosynthetic-to-heterotrophic cells were associated with maxima in NH₄⁺ concentrations. These observations imply that the Southern Ocean 27 becomes a biological source of CO₂ to the atmosphere in autumn and winter, not only because nitrate drawdown is weak, but also because the ambient conditions favour net heterotrophy and NH₄⁺ accumulation. High wintertime surface NH4 + concentrations, and the drivers of biological NH4 + cycling, may also have implications for nitrate uptake, through inhibition, and for the air-sea flux of ammonia gas, with the latter influencing the formation of aerosols, clouds, and climate.